Evaluation of families derived from backcrosses of processed tomato with dwarfism gene - Cavasin,Pedro Yuri (2021)
Abstract In comparison to tomato plants without the dwarfism gene, dwarf tomato plants were shorter, had a smaller canopy diameter and remained upright during maturation, thereby reducing the fruit-soil contact, resulting in healthier fruits. This study evaluated tomato families of a BC1F3 population carrying the dwarf gene for industrial yield. The 150 BC1F3 families and the two parents (hybrid H-9889 and accession BGH-9889) as controls were assessed in an augmented block design with four replications. The data were subjected to variance analysis and the F test. A selection index, based on the sum of ranks of Mulamba and Mock (1978), was used for the selection of genotypes, considering the most relevant traits, i.e., canopy diameter, yield, lodging and fruit firmness. Thus, selection resulted in a yield gain of 8.04%.